2020
DOI: 10.1002/dta.2889
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of high‐purity N,N‐dimethyltryptamine hemifumarate for human clinical trials

Abstract: Since 2006, there has been a resurgent interest in the pharmacology and therapeutics of psychedelic drugs. Psilocybin, the 4-phosphoryl ester of N,Ndimethyltryptamine (DMT), has been studied most often, but DMT itself is also appealing because of its brief but profound psychological effects and its presence as an endogenous substance in mammalian brain. Although there have been a few studies of ayahuasca, a DMT-containing water infusion, only one human study with pure DMT has been reported since the early 2000… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 69 publications
0
7
0
Order By: Relevance
“…The first described synthesis of 1 converted tryptamine 2 via alkylation with methyl iodide . The synthetic approaches to deliver 1 have been reviewed, while the synthesis and characterization of 1 hemifumarate for human clinical trials have been reported . Three potential routes were considered, as illustrated in the retrosynthesis shown in Scheme .…”
Section: Design and Synthesis Of The Dmt Derivativesmentioning
confidence: 99%
See 1 more Smart Citation
“…The first described synthesis of 1 converted tryptamine 2 via alkylation with methyl iodide . The synthetic approaches to deliver 1 have been reviewed, while the synthesis and characterization of 1 hemifumarate for human clinical trials have been reported . Three potential routes were considered, as illustrated in the retrosynthesis shown in Scheme .…”
Section: Design and Synthesis Of The Dmt Derivativesmentioning
confidence: 99%
“…An initial comparison of routes (5 g) starting with indole 3 or 4 indicated little difference between the routes in terms of output yield and purity compared to previously reported yields. 45 However, the route starting with 4 was favored as it starts from the inexpensive and readily available starting material auxin, has a shorter overall route (isolation of intermediate not required), uses low toxicity reagents (1-ethyl-3-carbodiimide (EDC) and 1-hydroxybenzotriazole (HOBt) versus oxalyl chloride), and required less LiAlH 4 in the second step (0.9 equiv versus 2.0 equiv) when compared to the double reduction of β-keto-amide 5.…”
mentioning
confidence: 99%
“…There were two papers in this review that aimed to create salt forms of psychedelic substances. Cozzi and Daley ( 86 ) made DMT hemifumurate salt and Sherwood et al ( 84 ) made 5-MeO-DMT succinate salt; these are both molecules that have been used significantly less in clinical trials compared to psilocybin. Previous research investigating consumption of DMT and 5-MeO-DMT in a naturalistic setting noted that the administration for these substances have primarily been through oral administration of ayahuasca for DMT ( 144 ) and the inhalation of vapour for 5-MeO-DMT ( 136 , 137 ).…”
Section: Discussionmentioning
confidence: 99%
“…Two research groups used 1 H NMR spectroscopy during the process of synthesising psychedelic molecules into their water-soluble salt forms. Sherwood et al ( 84 ), synthesised 5-MeO-DMT succinate salt and Cozzi and Daley ( 86 ) synthesised DMT hemifumarate salt. The reactions used to synthesis these molecules were different; 5-MeO-DMT succinate salt was produced using a Fischer indole reaction, whereas the DMT hemifumarate salt was produced with a Speeter and Anthony approach.…”
Section: Methodsmentioning
confidence: 99%
“…His nigerine was later identified as being the same as Manske's DMT (Bigwood & Ott, 1977;Ott, 2002), which Szára would only start studying after reading about its presence in the South American psychoactive snuff cohoba (Winter, 2019). If there are current attempts to develop DMT through large-scale synthesis for therapeutic purposes (Cozzi & Daley, 2020), and if it includes patenting, indigenous knowledge and rights should not once again be disrespected. Importantly, this kind of process can also be considered extractive, colonial, and traumatizing to indigenous people (Fotiou, 2020;George et al, 2020).…”
Section: Consequences Of the Epistemic Injustice For Indigenous Peoplesmentioning
confidence: 99%